LIVABILITY AND RECOVERY RATE OF BALI CATTLE SPERMATOZOA DURING PRESERVATION IN TRIS-BASED EGG YOLK DILUENT WITH DIFFERENT SUCROSE LEVELS - Yendraliza Yendraliza; Tania Tania; Restu Misrianti; Zumarni Zumarni (Jurnal Kedokteran Hewan, 2019)
This study aimed to determine the effect of sucrose addition in tris-based egg yolk diluent in maintaining and protecting spermatozoa during preservation. The design of this study was a completely randomized design (CRD) which consisted of five treatments with ten replications. The treatments were tris-based egg yolk diluent without sucrose (P0, control), tris-based egg yolk diluent with 0.2% sucrose (P1), tris-based egg yolk diluent with 0.3% sucrose (P2), tris-based egg yolk diluent with 0.4% sucrose (P3) and tris-based egg yolk diluent with 0.5% sucrose (P4). The parameters measured were motility, livability, abnormality, intact plasma membrane, and recovery rate. Semen was evaluated 2 times, freshly after being collected and post thawed. The results showed that the increase level of sucrose addition from 0.2% to 0.5% increased the motility value from 43.59% to 48.15%, the livability value from 51.24% to 55.45%, the intact plasma membrane value from 44.66% to 48.21%, the recovery rate value from 54.6% to 60.2 %, and reduce the abnormality value from 13.49%-10.24%. It can be concluded that the addition of 0.2- 0.5% sucrose in tris-based egg yolk diluent could increase motility, livability, intact plasma membrane, recovery rate, and could reduce the abnormalities of Bali cattle spermatozoa during preservation